Do giant molecular clouds care about the galactic structure?. Issue 1 (4th February 2014) - Fujimoto, Yusuke; Tasker, Elizabeth J.; Wakayama, Mariko; Habe, Asao
Abstract: We investigate the impact of galactic environment on the properties of simulated giant molecular clouds (GMCs) formed in an M83-type barred spiral galaxy. Our simulation uses a rotating stellar potential to create the grand design features and resolves down to 1.5 pc. From the comparison of clouds found in the bar, spiral and disc regions, we find that the typical GMC is environment independent, with a mass of 5 × 10 5 M⊙ and radius 11 pc. However, the fraction of clouds in the property distribution tails varies between regions, with larger, more massive clouds with a higher velocity dispersion being found in greatest proportions in the bar, spiral and then disc. The bar clouds also show a bimodality that is not reflected in the spiral and disc clouds except in the surface density, where all three regions show two distinct peaks. We identify these features as being due to the relative proportion of three cloud types, classified via the mass–radius scaling relation, which we label A, B and C . Type A clouds have the typical values listed above and form the largest fraction in each region. Type B clouds are massive giant molecular associations (GMAs) while type C clouds are unbound, transient clouds that form in dense filaments and tidal tails. The fraction of each clouds type depends on the cloud–cloud interactions, which cause mergers to build up the GMA type B s and tidal features in which the type C clouds are formed. The number of cloud interactions is greatest in the bar, followed by the spiral, causing a higher fraction of both cloud types compared to the disc. While the cloud types also exist in lower resolution simulations, their identification becomes more challenging as they are not well-separated populations on the mass–radius relation or distribution plots. Finally, we compare the results for three star formation models to estimate the star formation rate and efficiency in each galactic region.